2021
DOI: 10.1108/mrr-01-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of message framing on the links between organizational identification and unethical pro-organizational behavior

Abstract: Purpose The purpose of this study is to examine how – if any – does message framing moderates the previously documented positive effect of organizational identification on unethical pro-organizational behavior (UPB). Design/methodology/approach The authors used vignette methodology to manipulate message framing and organizational identification in a 2 × 2 between-subjects experimental design to test research hypotheses. In total, 332 undergraduate students in the senior year of banking and management partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…UPB intentions are elicited in varied magnitudes by managerial communication that highlights a potential benefit or loss [17]. Our findings take the work of [18] one step further and examine UPB from the framework of identification-LMX and leadership communication interaction. Specifically, our findings indicate that a loss framed message from the leader amplified the positive effect of LMX on UPB, while it diminished the effect of organizational identification.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…UPB intentions are elicited in varied magnitudes by managerial communication that highlights a potential benefit or loss [17]. Our findings take the work of [18] one step further and examine UPB from the framework of identification-LMX and leadership communication interaction. Specifically, our findings indicate that a loss framed message from the leader amplified the positive effect of LMX on UPB, while it diminished the effect of organizational identification.…”
Section: Discussionmentioning
confidence: 88%
“…In a similar vein, under fierce competition, followers who receive a positively framed message from their leaders can be over-inspired to achieve organizational goals. Based on an experimental study with a student sample, [18] have shown that leader's communication style is likely to influence the relationship between followers' organizational identification and willingness to participate in UPB. Nevertheless, the way a leader frames a message may have varying effects on UPB depending on followers' interactions with the leader, too.…”
Section: The Moderating Role Of Message Framingmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, organizational identification, or the perception of oneness or belongingness with the organization (Ashforth & Mael, 1989), has been the most widely examined antecedent of UPB to date. In all, 12 empirical studies found a significantly positive relationship between organizational identification and UPB (Alniacik et al, 2021; Baur et al, 2020; Chen et al, 2016; Effelsberg et al, 2014; Irshad & Bashir, 2020; Johnson & Umphress, 2019; Kalshoven et al, 2016; Kim et al, 2015; Kong, 2016; Mahlendorf et al, 2018; Naseer et al, 2020; Niu et al, 2020; Yang et al, 2019). One study reported mixed evidence for this link (May et al, 2015), while another study found that organizational identification was significantly related to UPB only when individuals had high (vs. low) positively reciprocity beliefs, which relate to the degree to which individuals endorse reciprocity in exchange relationships (Umphress et al, 2010).…”
Section: Theoretical Perspectives and Empirical Research On Upbmentioning
confidence: 99%
“…Further, previous studies have shown the strength of association between organizational identification and UPB is dependent on moderating variables like message framing (Alniacik et al, 2022), interorganization competition (Chen et al, 2016) and disposition toward ethical/ unethical behavior (Effelsberg et al, 2014). To expand this body of research, it would be meaningful to examine the impact of other personality variables which may impact employees' engagement in UPB when their organizational identification is high.…”
Section: Introductionmentioning
confidence: 99%